If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 6 + 8m = -5 + 2m + -1 Combine like terms: -6 + 6 = 0 0 + 8m = -5 + 2m + -1 8m = -5 + 2m + -1 Reorder the terms: 8m = -5 + -1 + 2m Combine like terms: -5 + -1 = -6 8m = -6 + 2m Solving 8m = -6 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 8m + -2m = -6 + 2m + -2m Combine like terms: 8m + -2m = 6m 6m = -6 + 2m + -2m Combine like terms: 2m + -2m = 0 6m = -6 + 0 6m = -6 Divide each side by '6'. m = -1 Simplifying m = -1
| -6.9=y+5.8 | | 5x+-7=4x+-1 | | 7.1x-2.6x= | | 1/8+5/7 | | x-.25x=16.50 | | -28=5(d-91)-53 | | 6y-6x=15 | | 6m-11+3m= | | 350D=735 | | (q+6)=(q*5(q-3)) | | -8-7a+2+5a=4 | | 6=0.83v | | 23x+74x=55 | | 289+48h+f=2 | | .4x+2=.2x+11 | | p/-3=-2.8 | | 63/7x63 | | 10x+15=8x+15 | | 5u-2/u+12 | | 7.1x+2.6x= | | y=c-ay-by | | -2y+12-3y=24-2 | | 1/2=3x-6 | | x^2-2x+91=0 | | -8b+9b=-20 | | 3b+7=2 | | 8/x+12=2x+6 | | 9-2(3x-4)=21 | | -20x^2y^4+28xy^4+24y^4= | | 2/3p=14 | | 10+(887(463x356))+57/8 | | 1/3p-3/8p=3 |